Penning pigs: Pig rearing practices, biosecurity measures, and outbreaks of African swine fever in central Uganda - Thompson, Rebekah (Society for Applied Anthropology, 2021)
In this article, I explore why a number of smallholder pig farmers in central Uganda decided not to implement the biosecurity measures advocated by veterinarians. I focus on the infectious disease, African swine fever, to illustrate how the biosecurity measures intended to limit the risk of disease, inadvertently constrained the future returns on pigs for farmers and their families. I draw on ethnographic research from Mukono, a district in central Uganda, to show how farmers considered pigs to be “quick money”—a type of household wealth that could be rapidly generated and liquidated with ease. I suggest that farmers’ conceptualization of their pigs as a specific type of wealth influenced the ways in which they integrated pigs into their lives and homes. Based on smallholder farmers’ accounts, I conclude this article by calling for a reconsideration of biosecurity measures as a universal solution for controlling diseases on farms. I argue that instead of designing protocols that separate species, disease prevention strategies need to recognize the ways in which different livestock animals become part of farmers’ lives and acknowledge how this influences farmers’ disease management practices.